(3OhQ GdGJMGO GdGaQjbj aj MaX GdSde h GdCef GdOhdjjf (B: s (3OQGSI JWHjbjI Ydi MGdI OGQahQ (B/ s - (3NGdO CQMjeI EHQGgjes; (3CMeO CHhGdhaG s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3JfGhd gPG GdHMK OQGSI GdGJMGO GdGaQjbj aj MaX GdSde h Gdef GdOhdjjf OQGSI JWHjbjI dCReI Ebdje OGQahQ (B: (3MjK LGAJ GdOQGSI ebSeI Edi HGHjf bSe cd efgeG Edi aUdjf (B: (3MjK JfGhd GdHGH GdChd (B: (3bhGYO MaX GdSde h GdCef GdOhdjjf aj GdGJMGO GdGaQjbj (B: (3h BdjGJ GdMeGjI (B: (3Ke JfGhd GdHGH GdKGfj OQGSI JWHjbjI dMGdI Ebdje OGQahQ (B: (3h YQV ajg dCReI OGQahQ h GdeMceI GdLfGFjI GdOhdjI (B: (3h Hjf OhQ GdCee GdeJMOI (B: (3h LGeYI GdOhd GdYQHjI (B: (3h GdGJMGO GdGaQjbj (B: (3h ChVM GdUYhHGJ GdJj hGLgJ GdGJMGO GdGaQjbj aj CReI Ebdje OGQahQ (B: (3h GdUYhHGJ GdJj JhGLg GdGJMGO aj MaX GdSde h GdCef HTcd YGe OGNd GdGJMGOs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdis
Keywords: (3CLgRI GdGJMGO GdCaQjbj GdeJYdbI HMaX GdSde hGdCef GdOhdjjfs; (3GdGJMGO GdGaQjbjs; (3EOGQGI GdGJMGO GdCaQjbj ddfRGYGJ GdCaQjbjI GdOGNdjI hGdOhdjIs; (3GdCHYGO GdbGfhfjI dCReI Ebdje OGQahQs; (3CReI OGQahQ hGdeMceI GdLfGFjI GdOhdjIs; (3OhQ efXeI GdCee GdeJMOI aj JShjI CReI Ebdje OGQahQs; (3OhQ LGeYI GdOhd GdYQHjI aj JShjI CReI Ebdje OGQahQs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs